ANALISIS PERMINTAAN DAGING AYAM BROILER DI PASAR CIKURUBUK TASIKMALAYA PADA MASA PEMULIHAN EKONOMI SELAMA PANDEMI COVID 19 - Finadia Raihan Siti Afifah; Achmad Firman; Syahirul Alim (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
This study aims to analyze the level of demand of broiler chicken during the post-Covid 19 economic recovery period at Cikurubuk Traditional Market Tasikmalaya and analyze the factors that influence demand of broiler chicken meat. This research was conducted in May-June 2022 located in Cikurubuk Traditional Market, Mangkubumi, Tasikmalaya City. This research was conducted by means of a survey to 175 respondents who bought broiler chicken meat. The analytical method used in this research is multiple linear regression analysis method using SPSS 21 IBM tool. The results showed that the demand for broiler chicken during the post-Covid 19 economic recovery period was 4.9 kg/household/month. The factors that significantly influence the demand for broiler meat during the post-Covid 19 economic recovery period at the Cikurubuk Traditional Market Tasikmalaya are the price of rice, monthly household income and the number of family member.